Looking for the Brain Inside the Initial Teacher Training and Outreach Books in Portugal - Rato, Joana R.; Amorim, Jorge; Castro-Caldas, Alexandre (Frontiers in Psychology, 2022)
The fascination with brain research is widespread, and school teachers are no exception. This growing interest, usually noticed by the increased supply of short-term training or books on how to turn the brain more efficient, leads us to think about their basic training and outreach resources available. Little is known about what the official Initial Teacher Training (ITT) offers concerning the brain literature and if it meets scientific standards. Also, what are the science communication materials that teachers can access to learn about the developing brain remain undiscussed. First, we examined the ITT courses taught in Portuguese Higher Education, both in public and private institutions, to identify the syllabus with updated neuroscientific knowledge. Second, we searched for the neuroscience-related books published in the last 6 years through the National Library of Portugal database. Thirty ITT courses and 35 outreach publications were reviewed through a rapid review methodology. Our results showed an absence of curricular units indicating in their programs that brain research, and its relationship with learning, would be taught in a representative and updated way. In contrast, the number of brain-related books for educators increased in Portugal, corroborating the demand for this field of study by these professionals. Based on the literature that shows how misunderstandings about the brain have increased in school contexts, our discussion recognizes that science outreach could be a way to increase the scientific literacy of school teachers with the research community working more in this direction, but, since a previous problem seems to be unsolved, there is an urgent need for specialized attention to the development of training curricula for future kindergarten and elementary school teachers.